Strategi Penguatan Motivasi Belajar Berbasis Nilai Trilogi dan Panca Kesadaran Santri di SMP Nurul Jadid - Misbahul Arifin (Educational Research Indonesia, 2025)
This study explores strategies to strengthen students’ learning motivation based on the Trilogy of Santri and the Five Awarenesses of Santri at SMP Nurul Jadid, Probolinggo. The research addresses the issue of low learning motivation, seen in students’ limited participation, low initiative, and weak academic discipline. Using a qualitative case study approach through interviews, observations, and documentation, the study examines how the Trilogy of Santri—fardhu ‘ain awareness, avoidance of major sins, and noble character—and the Five Awarenesses—religious, scientific, social, national, and organizational—can enhance motivation. The findings show that integrating these values improves students’ discipline, academic responsibility, intrinsic motivation, and active engagement in learning and community life. The study concludes that strengthening learning motivation through religious and moral foundations provides an effective model for modern Islamic education, fostering balanced intellectual, spiritual, and social development among students